The simplest signal detection algorithms of transition process of tension in power lines - S. I. Novikov; I. L. Kuz'min; R. G. Khuzyashev (Известия высших учебных заведений: Проблемы энергетики)
In paper the algorithm of registration of a signal of transition process which is given rise both by single-phase short circuit on the earth and is described by normal switching processes. Registration is performed by means of tension sensors which are established on an overhead power transmission line. The efficiency evaluation of the offered algorithm was made by comparison with the known signal detection algorithms in two parameters: in the maximum size of the relation a signal/hindrance and by the number of computing transactions. It is shown that the offered algorithm of the digital filter of the sensor occupies smaller resources of memory and requires smaller computing capacities of the microcontroller, and in too time allows to register reliably transitional process.